If you want to see a whale - Fogliano, Julie; Stead, Erin E. (New York : Roaring Brook Press, 2013)
Advises the reader about what to do, and not do, in order to successfully spot a whale, such as wrapping up in a not -too-cozy blanket, ignoring the roses, and especially, being patient
"A Neal Porter Book."
Keywords: Whale watching -- Juvenile fiction; Patience -- Juvenile fiction; Whale watching -- Fiction; Patience -- Fiction